Retrospective study of outcome in patients with scorpion sting using prazosin with/without dobutamine - Venugopal, L; Anilkumar, H; Ram Pure, Dilip M; Kumar, L Suresh; Rajashekharappa, G (Asian Journal of Medical Sciences, 2015)
Introduction: Scorpion sting is a major public health problem in India with severe life threatening complications. Toxin can cause autonomic overstimulation leading to hypertension, arrhythmias and pulmonary edema with left ventricular dysfunction. Prazosin has been the ideal antidote for patients with mild to moderate envenomation. In patients with severe envenomation, dobutamine is found to be very useful to prevent morbidity and mortality. Materials and Methods: Retrospective study was done on patients admitted from March 2011 to November 2013 with a history of scorpion bite and adults aged between 20-60 yrs were included. All the patients were subjected to grading of envenomation as mild, moderate and severe degree. Prazosin was given to all 80 patients and dobutamine was given to those who did not show response to prazosin. Results: Majority of patients were in the age group of 31-40 years followed by 21-30 years. Mean age was 31.23±7.23 years. Fifty four patients (67.5%) were male and twenty six (32.5%) were female. 28 patients had mild envenomation, 36 had moderate envenomation and 16 had severe envenomation. 83.33% of patients responded to dobutamine infusion in prazosin resistant cases in our study. Conclusion: Early use of dobutamine should be considered in patients with severe envenomation with left ventricular dysfunction to prevent morbidity and mortality. 2D echo has to be considered to assess left ventricular dysfunction and need for early use of dobutamine. Asian Journal of Medical Sciences Vol.7(2) 2015 61-63